PERAN TOKOH MASYARAKAT DALAM MENGIMPLEMENTASIKAN NILAI SILA PERSATUAN INDONESIA DI DESA PATERONGAN GALIS BANGKALAN - Hasyim, Fuad; Imam Faisal, Bagus; Sunardjo; Ernawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the role of community leaders in implementing the values of the third precept of Pancasila, namely Indonesian Unity (Persatuan Indonesia), in Paterongan Village, Galis District, Bangkalan Regency. This research uses a qualitative descriptive approach with a case study method. Data were collected through in-depth interviews, direct observation, and documentation involving three informants: the village head, a community leader, and a village resident. Results show that community leaders play a significant role as role models, motivators of cooperative activities (gotong royong), conflict mediators, and social facilitators. Supporting factors include authority, trust, exemplary behavior, communication skills, and village government support. Inhibiting factors include social media influence and individualistic attitudes. Community leaders hold a strategic position in strengthening Indonesian Unity values through concrete daily social actions.